2006
DOI: 10.2134/agronj2005.0041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spring Application of a Paper Mill Soil Conditioner on Corn Yield

Abstract: Use of paper mill residuals as soil amendment on farmland is believed to have a beneficial impact on crop yields and soil quality. The objective of our study was to evaluate the effect of spring applying Domtar Soil Conditioner (SC) (pulp and paper mill waste water treatment residue) to a sandy soil in eastern Ontario, Canada. The effects of SC on corn (Zea mays L.) yields, N concentrations in plants, and post-harvest levels in soil of NO 3 , P, K, Mg, organic matter (OM), and pH were investigated. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
(26 reference statements)
0
28
1
2
Order By: Relevance
“…Improved soil properties such as increased organic matter (Table 2) and its related effect on soil water availability, microbial activity and aggregation (Zibilske et al 2000;Gagnon et al 2001;Foley and Cooperband 2002;N'Dayegamiye 2006) may also be involved. Beneficial effects of several annual PB applications on corn yield have been reported (Curnoe et al 2006;N'Dayegamiye 2006). (Table 3).…”
Section: Crop Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved soil properties such as increased organic matter (Table 2) and its related effect on soil water availability, microbial activity and aggregation (Zibilske et al 2000;Gagnon et al 2001;Foley and Cooperband 2002;N'Dayegamiye 2006) may also be involved. Beneficial effects of several annual PB applications on corn yield have been reported (Curnoe et al 2006;N'Dayegamiye 2006). (Table 3).…”
Section: Crop Yieldmentioning
confidence: 99%
“…In a 5-yr study on corn production, Curnoe et al (2006) reported that the concentration of NO 3 -N in the first 15 cm of a sandy loam increased with time and with increased PB application rate up to 25 Mg dry ha…”
Section: Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, research examining the effect of PB amendments on crop growth and yield has been conducted on winter cabbage (Brassica oleracea var. capitata L.) (Simard et al 1996;Simard 2001), barley (Hordeum vulgare L. Chapais) (Simard et al 1998), potato (Solanum tuberosum L. Hilite Russet) (Lalande et al 2003), and corn (N' Dayegamiye et al 2003;Curnoe et al 2006). Crop yield responses to PB applications have been variable.…”
mentioning
confidence: 99%
“…For instance, paper pulp and mushroom production is not seasonal, whilst olive processing is mostly carried out in the winter months. Regardless of this, by-products from these three industries have been successfully tested for their uses in crop production [22,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%